2019
DOI: 10.1039/c8ta11704g
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic frameworks: a promising platform for constructing non-noble electrocatalysts for the oxygen-reduction reaction

Abstract: This review provides an overview of crucial roles that MOFs have played in constructing non-noble ORR catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
90
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(91 citation statements)
references
References 246 publications
1
90
0
Order By: Relevance
“…Based on these values, we can concluded that the ORR activity of FeNC/rGO is comparable with that of commercial Pt/C (20 wt %) catalyst. Noteworthy, these values are also in the top ranks of catalytic activity among non‐noble catalysts towards ORR . In the acid medium (0.5 m H 2 SO 4 ), this catalyst also exhibited a considerably high ORR activity, with an Eon‐set of 0.86 V vs. RHE and an E1/2 of 0.72 V vs. RHE (seeing the LSV profiles in Figure S4 in Supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…Based on these values, we can concluded that the ORR activity of FeNC/rGO is comparable with that of commercial Pt/C (20 wt %) catalyst. Noteworthy, these values are also in the top ranks of catalytic activity among non‐noble catalysts towards ORR . In the acid medium (0.5 m H 2 SO 4 ), this catalyst also exhibited a considerably high ORR activity, with an Eon‐set of 0.86 V vs. RHE and an E1/2 of 0.72 V vs. RHE (seeing the LSV profiles in Figure S4 in Supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, there has been much interest in metal–organic framework (MOF) materials as crystalline porous hosts for gas adsorption, separation and catalysis 24 26 . Their high surface area, potentially active metal centres, diverse pore structure and, in exceptional cases, their redox activity, promote their use as electrocatalysts for H 2 and O 2 evolution and reduction of O 2 27 29 . However, highly crystalline MOFs with fully coordinated metal centres exhibit only low charge-transfer ability and formally no active centres for electrocatalysis 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The tunable pore nature and constituents of MOFs systematically introduce different redox‐active and auxiliary centers to tune the catalytic properties for highly efficient and selective catalysis . MOFs have also been used in electrocatalysis, such as for the oxygen reduction reaction, hydrogen evolution reaction, electroreduction of CO 2 , and electrooxidation of ethanol . However, the inherent low conductivity of most MOFs heavily deteriorates their electrocatalytic properties, especially in electroorganic synthesis.…”
Section: Introductionmentioning
confidence: 99%